Pelatihan Pembuatan Soal Berbasis HOTs Menggunakan Socrative di MA Nurul Iman Mahato - Pariang Sonang Siregar; Rindi Genesa Hatika (Universitas Mathla'ul Anwar Banten, 2021)
TRAINING ON MAKING HOTS-BASED QUESTIONS USING SOCRATIVE AT MA NURUL IMAN MAHATO. Permendiknas Nomor 16 Tahun 2007 regarding Academic Qualification Standards and Subject Teacher Competencies states that subject teacher competence includes developing assessment instruments. Therefore, the position of the learning outcome assessment instrument is very strategic in making teacher and school decisions related to the achievement of student learning outcomes including high-order thinking skills. The success of using HOTS-based questions so that they can be favored by students is also supported by the use of information communication technology. Socrative is a student response system that allows teachers to create interactive quizzes or games and engage students directly. Madrasyah Aliyah (MA) Nurul Iman Mahato is one of the schools that has not implemented HOTs-based question making using Socrative as a learning outcome evaluation tool, while one of the teacher's abilities that must be possessed and is the most important part is the ability to make and develop learning outcome evaluation tools. students. Based on the results of the PKM implementation that has been implemented, it can be concluded that community service activities on HOTs-based Question Making Training Using Socrative are very beneficial to the participants and the participants are also enthusiastic about participating in this program.